2023
DOI: 10.1111/epi.17664
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, oscillations, and epilepsy

Abstract: Sleep and wake are defined through physiological and behavioral criteria and can be typically separated into non‐rapid eye movement (NREM) sleep stages N1, N2, and N3, rapid eye movement (REM) sleep, and wake. Sleep and wake states are not homogenous in time. Their properties vary during the night and day cycle. Given that brain activity changes as a function of NREM, REM, and wake during the night and day cycle, are seizures more likely to occur during NREM, REM, or wake at a specific time? More generally, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…People with epilepsy often experience disruptions in their sleep architecture ( Bernard et al, 2023 ). However, previous research found no correlation between nighttime sleep architecture or interruptions of sleep and a 24 h delayed recall of verbal and non-verbal memory in people with epilepsy ( Fitzgerald et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…People with epilepsy often experience disruptions in their sleep architecture ( Bernard et al, 2023 ). However, previous research found no correlation between nighttime sleep architecture or interruptions of sleep and a 24 h delayed recall of verbal and non-verbal memory in people with epilepsy ( Fitzgerald et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The network effects of tDCS are also dependent on brain state, with cathodal tDCS having greater effects during a task while anodal tDCS has greater effects during rest ( Li et al, 2019 ). Epileptic brain activity, both seizures and IEDs, are often more prevalent during certain states of arousal such as sleep in both focal epilepsy and in GGE ( Bernard et al, 2023 ). This shows that the probability of epileptic activity is modulated by the global state of the brain which relates to cortical excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Another study looking at continuous intracranial electroencephalography and seizure diaries in patients with focal epilepsies found 5 seizure peak times (12 a.m., 3 a.m., 9 a.m., 2 p.m., and 6 p.m.) (9). Additionally, interictal activity may be associated with a circadian pattern that is specific to the individual patient (10). In a study of the association between interictal epileptiform activity and circadian and multidien rhythms, variability was shown among patients with epilepsy; however, stability was shown for individual patients for many years (11).…”
Section: Circadian Patterns Of Seizuresmentioning
confidence: 99%